Determinação da fluência do concreto e do coeficiente de Poisson diferido em um estado de tensões de compressão bi-axial - Maia, Antonio Claudio Ferraro (1974)
Present and analyse the first results of direct strain measurement in the concrete of the test slab (prestressed slab in two directions) of the Laboratório de Estruturas do Centro de Tecnologia da Universidade Federal do Rio de Janeiro. The purpose of the work is to observe the creep of the concrete and the change with time of Poisson's ratio relative to instantaneous and deferred deformations in plane stress. The safety check in the serviceability limit state and in the ultimate limit state of the test slab under systems of self-equilibrated forces are presented in parallel in this work. The set of employed instruments consisted of 31 Carlson electric strain gauges and 12 supports for readings with removable mechanical strain gauges "deformeter Huggenberger". The observation period corresponding to the results presented is between the concrete placing and one year after prestressing. The change in temperature which occurs in mass concrete during cement hydration and along of time is presented in graphical form. The Principles and Recommendations of the Comité Européen du Béton (CEB) and of the Fédération Internationale de la Précontrainte (FIP) were used in this research, in an attempt to establish a comparison of some experimental results with those proposed by the Recommendations.